Dampak Program Training Terhadap Peningkatan Keunggulan Kompetitif Perusahaan (Studi Kasus Pada Hotel Sofyan Inn Altama syariah Pandeglang ) - Ahyakudin Ahyakudin (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research is to analyze the importance of training and training system at Sofyan Inn Altama Hotel Syariah. Data analysis method used in this research is qualitative method. The results showed that the Company generally conducts training or training activities in order to obtain qualified employees in skill, knowledge, and good attitude in organizing.Sofyan Inn Altama syariah hotel implemented training to tie softskill, hartskill and knowledge management of its employees. To assess the success of training, it is necessary to have an appropriate systematic evaluation. This is to be taken into consideration whether the contract of work will be continued or terminated within a specified time. The success of training can be seen from the success indicator of the training set at Sofyan Inn Altama shariah hotel.